ANALISIS EFISIENSI DAN EFEKTIVITAS PAJAK HOTEL DAN RESTORAN DALAM UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN SERAM BAGIAN TIMUR - Muhammad Ramli Faud (AkMen JURNAL ILMIAH, 2015)
Effectiveness and efficiency, contribution analysis, revenue daerah.Penelitian is a case study in East Seram District entitled "Effectiveness and Efficiency Analysis of Local Tax Revenue Increase In Effort East Seram District The aim of this study to analyze and provide solutions to the effectiveness and efficiency of tax revenue daerahserta to analyze the contribution of local tax revenues to total local revenues East Seram District analysis tool is used is to calculate and analyze the effectiveness and efficiency of each local taxes as well as calculate and analyze the contribution of each to the total local taxes and local taxes total local revenues in East Seram District The results of calculation from 2009 through 2014, the local tax is always effective is the restaurant tax, entertainment tax and advertisement tax. For hotel tax, street lighting tax, and the tax registration of the company there are in a given year effectiveness rate calculation results are not 100% effective and it means not the tax collection. For the calculation of the level of efficiency of street lighting tax only the most efficient, while other local taxes in Banjarmasin can be said in general is not efficient because the costs incurred in excess of the permissible batasmaksimal 5%. Calculation of the contribution each. each local taxes to total tax area as a whole suggests that the contribution of each year is always fluctuating, there are increasing and there is decreased. Daerahterhadap tax contribution of local revenues also constantly fluctuating, although when viewed regional tax revenue each year is increasing. From the analysis it can be concluded that the level of effectiveness of local taxes are high in East Seram District proven to increase revenue, although there are some areas that particular year tax tax collection is ineffective. From the analysis of the level of efficiency, it can be concluded that the performance of local governments in the management of the costs of obtaining revenue from local taxes not everything can be said to be efficient. For local taxes that provide the greatest contribution is tax and street lighting that gives the smallest contribution is tax registration of companies. Of the total revenue, the largest contribution comes from local tax revenue. Each year local tax contribution to reach 50% of the overall total revenue aslidaerah. Based on the above conclusion, it should be repaired again the performance of tax collection area. The effectiveness and efficiency always endeavored to increase each year so that it will have an impact on increasing local revenue district sinister East Section